Summary Proceedings of the Fifty-Second Annual Meetings of the Board of Governors, September 23-25, 1997. (Summary Proceedings; 52nd Annual Meeting, 1997, 1997)
This annual publication is a record of the IMF's Annual Meeting and contains the opening and closing addresses of the Chairman of teh Board of Governors, presentation of the Annual Report by the Managing Director, statements of Governors, committee reports, resolutions, and a list of delegates. Usually published in March. 1997 edition.